Strange, Rare and Peculiar Symptoms of COVID-19 Cases Managed by Practitioners of the Homeopathy Help Network - Pracjek, Parker; Gray, Alastair C.; Doherty, Rachael; Straiges, Denise (Homeopathy, 2023)
Background More than 670 million people have been infected by COVID-19. This case series reports 8 of 55 cases in a broader study of COVID-positive clients who sought homeopathic care for symptoms. Existing studies of homeopathy and COVID-19 have sometimes failed to employ the underpinning theoretical framework of homeopathy—the genus epidemicus. Special focus has been placed on standout symptoms not often reported in conventional medical outlets, known among homeopaths as “strange, rare and peculiar” (SRP) symptoms. The Homeopathy Help Network (HHN) team of practitioners noted SRP symptoms across dozens of cases and studied how they shifted collectively as different variants of the virus emerged.Methods COVID-positive individuals self-selected for individualized care for their symptoms using homeopathy. They received tele-health consultations and individualized homeopathy interventions in an out-patient homeopathy clinical setting. Clients were seen by individual professional homeopathy practitioners and students under supervision working at the HHN in the United States. Cases for the series were hand-picked with the aim of being an average representation of the more than 4,000 COVID-positive cases seen by members of the HHN. Cases in the full compendium are grouped according to a predominant case feature: Multiple remedies, Posology, Time ill, Single remedy resolution, Hospitalization and, in this case series, SRP symptoms.Results SRP symptoms included: continually on the verge of unconsciousness; dark green stools; very low pulse alternating with tachycardia; sensation of strong or burning chemical smells; sensation of inhaling water through the nose; recurring electric shock sensations in head or extremities; yellow-green stools.Conclusion Collective SRP symptoms from the pandemic provided the opportunity to study the hallmark features of COVID-19 in depth. The importance of these symptoms highlights the applicability of Hahnemannian principles and good case-taking practices.
Keywords: homeopathy; COVID-19; strange; rare; peculiar; characteristic; case series